2018
DOI: 10.1523/jneurosci.1918-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Puncta of Neuronal Nitric Oxide Synthase (nNOS) Mediate NMDA Receptor Signaling in the Auditory Midbrain

Abstract: Nitric oxide (NO) is a neurotransmitter synthesized in the brain by neuronal nitric oxide synthase (nNOS). Using immunohistochemistry and confocal imaging in the inferior colliculus (IC, auditory midbrain) of the guinea pig (Cavia porcellus, male and female), we show that nNOS occurs in two distinct cellular distributions. We confirm that, in the cortices of the IC, a subset of neurons show cytoplasmic labeling for nNOS, whereas in the central nucleus (ICC), such neurons are not present. However, we demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 64 publications
1
31
0
Order By: Relevance
“…The transfer function relating NO exposure to vasodilation, as well as the sensitivity of an arteriole to NO (m) was also taken to be time-invariant during the simulation; however, the dynamics of GC deactivation are slower than GC activation [ 207 209 ] and this is likely to produce long lasting effects that will not be captured by our model. Also, GC activation can occur at lower NO concentrations [ 210 , 211 ] or independently of NO signaling [ 212 ] which may play a role in other biological processes [ 213 ]. We did not model GC activation dynamics or the mechanical properties of the arteriole to obtain vascular responses but fitted the positive component of the transfer function to an empirically determined kernel from in vivo measurements [ 1 , 156 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transfer function relating NO exposure to vasodilation, as well as the sensitivity of an arteriole to NO (m) was also taken to be time-invariant during the simulation; however, the dynamics of GC deactivation are slower than GC activation [ 207 209 ] and this is likely to produce long lasting effects that will not be captured by our model. Also, GC activation can occur at lower NO concentrations [ 210 , 211 ] or independently of NO signaling [ 212 ] which may play a role in other biological processes [ 213 ]. We did not model GC activation dynamics or the mechanical properties of the arteriole to obtain vascular responses but fitted the positive component of the transfer function to an empirically determined kernel from in vivo measurements [ 1 , 156 ].…”
Section: Discussionmentioning
confidence: 99%
“…The major type in the VCN is the β form (Eliasson et al, 1997), which is located in the cytoplasm and lacks an initial pdz domain that would allow it to bind to the postsynaptic density protein (PSD-95 Brenman, Xia, Chao, Black, & Bredt, 1997). However, there is also some of the α variant which does have an initial pdz domain and can bind to the PSD-95 protein along with the NMDA receptor to form a multi-protein complex that includes guanylyl cyclase (Olthof-Bakker et al, 2019). In our study, almost half of the neurones responded to exogenous NMDA and seemed to have functional receptors.…”
Section: Discussionmentioning
confidence: 52%
“…The sections were then washed in buffer to halt the DAB reaction, mounted on coated slides, air-dried, dehydrated and cover-slipped. These were re-examined to study the distribution of nNOS staining and determine if it was associated with postsynaptic densities in the same way as for the inferior colliculus (Olthof-Bakker et al, 2019). We also separately stained 50 μm sections for Nissl substance with a standard cresyl violet stain (0.5% dissolved in 0.2 M acetate buffer at pH 3.9) to allow comparison of the density of neurones in the VCN.…”
Section: Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the microinfusion of NMDA‐receptor and NOS inhibitors in the IC has been shown to inhibit sound‐evoked electrocortical desynchronization, as measured by EEG in Iannone et al (1996), whereas the microinjection of the NOS inhibitor in the other relay stations of the acoustic pathway, such as the geniculatus medialis, lemniscus lateralis, and olivaris superior nuclei, was seen to have no effect (Nistico, Bagetta, Iannone, & Duca, 1994). In addition, findings from 2019 have shown that both the local delivery of the nNOS inhibitor N G ‐methyl‐L‐arginine (L‐NMMA) and the sGC inhibitor 1H‐[1,2,4]oxadiazolo[4,3‐a]quinolaxine‐1‐one (ODQ) blunts the NMDA‐evoked increase in sound‐driven activity of neurons in the IC using in vivo electrophysiological recordings (Olthof et al, 2019). In humans, hearing loss, which is sometimes associated with anosmia, constitutes a “red flag” for the diagnosis of syndromic forms of congenital hypogonadotropic hypogonadism, such as the Kallmann syndrome (Boehm et al, 2015), and is increasingly recognized as a risk factor for developing dementia (Bowl & Dawson, 2018).…”
Section: A Key Role For No In Modulating Neuronal Circuit Activity Inmentioning
confidence: 99%